Pengaruh Electronic Word Of Mouth (e-WOM) dan Harga Terhadap Keputusan Pembelian Sunscreen Facetology Pada Marketplace Shopee - Fauzi, Hanan; Nurhayaty, Ety (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
The beauty industry in Indonesia continues to grow, particularly in sunscreen products favored by consumers through marketplace platforms such as Shopee. This study aims to analyze the influence of electronic word of mouth (e-WOM) and price on the purchasing decisions of Facetology Sunscreen products. This research employs a quantitative approach using multiple linear regression analysis. The population of this study includes Facetology Sunscreen consumers on the Shopee Marketplace, with a sample of 96 respondents selected through purposive sampling techniques. Partial tests show that e-WOM (X1) has a significant effect on purchasing decisions (Y), with a t-value of 2.195, and price (X2) also significantly influences purchasing decisions (Y), with a t-value of 2.211. Simultaneously, both variables have a significant effect on purchasing decisions (Y), as indicated by an F-value of 7.002. It can be concluded that e-WOM (X1) and price (X2) significantly influence purchasing decisions, highlighting that positive reviews and competitive pricing are key factors driving consumers to choose Facetology Sunscreen products.